Measuring Blood Loss in Obstetric Hemorrhage. Issue 3 (May 2020) - Wisner, Kirsten
Abstract : Obstetric hemorrhage is a major contributor to maternal morbidity and mortality in the United States. Many of these deaths are preventable. Our maternity nursing expert, Dr. Wisner, reviews quantification of blood loss for all women after birth, based on recommendations from the Association of Women's Health, Obstetric, and Neonatal Nurses, and the American College of Obstetricians and Gynecologists.